Makna Motif Batik Tanjung Bumi Madura dalam Perspektif Unsur-unsur Keislaman - lulus Sugeng Triandika (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2021)
The Madurese people are described as very religious. Many of the cultural attributes reflect Islamic values. Islam has existed since the 15th century and has influenced various aspects of culture, one of which is Madurese batik. The existence of Islam in Madura has influenced the Tanjungbumi batik motif. Although Tanjungbumi Batik has a characteristic use of plant and animal characters, However Islamic elements are reflected in the motifs. So it is interesting to study in order to determine the influence of Islam in the Tanjungbumi batik motif. Although there have been many studies on Madurese batik, there has been little discussion about the patterns of batik motifs. This study uses a qualitative descriptive method through observation, literature study, and interviews with resource persons. Charles Sanders Peirce's visual semiotic analysis is used to study the object of research. Then conclusions are drawn based on data analysis. Keywords : Batik Motif, Tanjungbumi, Islamic Values, Stilation and Visual Semiotics